Ethnic Diversities, Hypertension and Global Cardiovascular Risk (Updates in Hypertension and Cardiovascular Protection,, 2018)
In the context of the most significant influx of migrants in European history, the objective of this book is to provide healthcare professionals with essential knowledge and skills to effectively treat and prevent cardiovascular diseases in ethnic minorities. Acknowledging that the scientific and cultural training of health professionals on the specific health needs of minority groups is still limited and likely biased, the book sheds light on the different health policies in European countries as well as epidemiologic data on cardiovascular events among migrants. In addition, it presents an in-depth analysis of potential ethnic-group-specific drivers of global cardiovascular risk within this new and challenging framework - as well as issues related to its prevention and treatment. The prevalence of hypertension, diabetes, chronic kidney disease, obesity, and metabolic syndrome is found to be higher among most minority groups than in the native population, yet their access to treatment and health services may be limited by cultural and language barriers. As health professionals are confronted with such intercultural challenges on a daily basis, specific training and dedicated publications are thus essential to accompany and foster a constructive development towards a pluralist and healthier society. This book addresses that need, offering a unique and revealing resource.